Maraknya Perceraian di Bawah Umur dan Peran Negara dalam Pencegahannya: The Rising Trend of Underage Divorce and the Role of the State in Its Prevention - Muhammad Adam HR; Reski Mulia; Muh. Adi Sucipto; Abdul Latif (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
The rising rate of divorce among young couples in Indonesia is closely associated with the persistently high prevalence of underage marriage, which results in households being formed under conditions of psychological, social, economic, and reproductive immaturity. This issue indicates that the state has predominantly emphasized its regulatory function through the establishment of a minimum legal age for marriage, yet has not optimally developed a preventive, educational, and protective system. This study aims to analyze the relationship between underage marriage and divorce among young couples, examine the inadequacy of the state’s role, and formulate strategies to strengthen the state’s function in preventing divorce. The research employs a qualitative method with a normative legal research design through statutory and conceptual approaches. Data were collected through library research and documentation and subsequently analyzed descriptively and analytically. The findings reveal that underage marriage systematically increases the risk of divorce by creating fragile households, while the state’s role remains ineffective due to the high number of marriage dispensations, weak premarital guidance, limited funding, and insufficient cross-sectoral coordination. This study formulates that strengthening the state’s role should be carried out through stricter control of marriage dispensations, competency-based premarital education, upstream prevention through schools and families, social protection, and post-marital assistance. The contribution of this study lies in positioning the state as the primary object of criticism while simultaneously offering a model for strengthening the state’s preventive, educational, and protective functions in developing integrated and sustainable resilience among young families.